(untitled) ("Conference on Universal Science Research 2023", 2023)
This chapter covers many procedures—often referred to as word creation processes in the literature—that enable language users to create new words, with a focus on processes involving the grammatical structure of words. By adapting a language’s vocabulary—and, less readily, its grammar—to fit the meaning they need to convey, speakers preserve the vitality and use of their languages. Users of language accomplish this in three main ways. Just as individuals import helpful things from other nations, one way to do this is to simply import a useful word from another language. This is how Japanese words like karaoke and Italian words like pizza became English words. These kinds of word circulation between languages are referred to as borrowings. Second, speakers of a language have the ability to alter the meaning of words that are already in the language to imply different things. The English term "sad," for instance, still means "unhappy," but it is also sometimes used to denote something akin to "pathetic." According to this new definition, a sad joke is one that doesn’t make you laugh out loud, not one that makes you cry.